Factors in job characteristics influence employees' motivation in the Johor Corporation / Nurnadiah Ibrahim - Ibrahim, Nurnadiah (Faculty of Business and Management, 2013)
Purpose - The purpose of this study was to examine the relationships between the factors in job characteristics with the employees' motivation and to examine the factors injob characteristics that influencing employees' motivation. Methodology -The study used stratified random sampling to select the sample size of respondents from employees in Johor Corporation. Data were collected on a structured questionnaire containing some demographic background of respondents, factors in job characteristics and employees' motivation. Then the data analyzed using descriptive statistical analysis, coefficient of reliability analysis and Pearson Correlation Coefficient analysis. Findings - Consistent with previous studies related to relationship between factors in job characteristics and employees' motivation, the study showed that all the factors in job characteristics (skill variety, task identity, task significance, job autonomy and feedback) have a positive significant relationship with employees' motivation. Conclusion - The research has proven that the factors in job characteristics have positive relationship with employees' motivation. However, factor in job characteristics that have the highest relationship with employees' motivation was feedback. As conclusion, there was positive relationship between factors in job characteristics with employees' motivation. Recommendation - For the future studies, it can be recommended to use a large population to get the more sample size of the respondents in order to ensure the studies can be used widely.